Uncertain external environment: business needs to cope quick - Awang, Naqiah; Rahman, Shamsinar (Universiti Teknologi MARA, Terengganu, 2022)
The biggest challenge of the external environment is the impact of Covid-19 that can be seen anywhere in every aspect of our life. Working from Home (WFH), online learning, shift in customer purchasing behavior and increase in public awareness about healthy lifestyle ring a loud bell requiring all businesses to change their business model. It seems that this pandemic will be prolonged in the future years thus, the business must have strategic planning to catch up. Even with the shift to the endemic phase now, people’s way of doing things has changed. Social distancing, queuing, and masking now is a must. Everything was done online from shopping, learning, working, meeting, exercising, and gathering. This had caused people’s reliance on the smartphone and other electronic devices have tremendously increased by force. As reported by The Malaysian Reserve, delivery service is now one of the core business activities with the widely adopted online ordering platform. The business will be left behind if they failed to associate these two critical business elements.